Gastrointestinal dysfunction in autism displayed by altered motility and achalasia in Foxp1+/− mice - Fröhlich, Henning; Kollmeyer, Marie Luise; Stuhlinger, Manuel; Niesler, Beate; Rappold, Gudrun (Proceedings of the National Academy of Sciences of the United States of America, 2019)
Gastrointestinal dysfunctions in individuals with autism spectrum disorder are poorly understood, although they are common among this group of patients. FOXP1 haploinsufficiency is characterized by autistic behavior, language impairment, and intellectual disability, but feeding difficulties and gastrointestinal problems have also been reported. Whether these are primary impairments, the result of altered eating behavior, or side effects of psychotropic medication remains unclear. To address this question, we investigated Foxp1+/− mice reflecting FOXP1 haploinsufficiency. These animals show decreased body weight and altered feeding behavior with reduced food and water intake. A pronounced muscular atrophy was detected in the esophagus and colon, caused by reduced muscle cell proliferation. Nitric oxide-induced relaxation of the lower esophageal sphincter was impaired and achalasia was confirmed in vivo by manometry. Foxp1 targets (Nexn, Rbms3, and Wls) identified in the brain were dysregulated in the adult Foxp1+/− esophagus. Total gastrointestinal transit was significantly prolonged due to impaired colonic contractility. Our results have uncovered a previously unknown dysfunction (achalasia and impaired gut motility) that explains the gastrointestinal disturbances in patients with FOXP1 syndrome, with potential wider relevance for autism.